Family health program in brazil: a focus on its basic assumptions, performance and advantages - Santana, Milena Lopes; Carmagnani, Maria Isabel (Saúde e Sociedade, 2001)
Since its conception up to the moment, many have been the analysis concerning the Family Health Program in Brazil (FHP). Although still in a small number, members of the Family Health Units, Health Municipal Secretaries, Mayors, members of health Ministry, as well as Universities teaching staff and renowned researchers of public health and other similar branches, they have disposed themselves towards discussing and considering such strategy. Thus, it became appropriate to carry out a review on the literature about The FHP, which was approached in topics: historic retrospective of the period that preceded The FHP; its basic assumptions; performance strategies; the family as the center of assistance, the principle of health vigilance, the performance of the multidisciplinarian staff, the different patterns of implantation in Brazil, the facilitating aspects or not of this launching in Brazil, as well as the advantages and disadvantages of The FHP in Brazilian Health System.